Factors Influencing Muslims to Choose Hibah: Empirical investigation using Logit Approach - Maamor, Selamah; Abd Wahab, Norazlina; Hashim , Suraiya; Zainol, Zairy (International Journal of Psychosocial Rehabilitation, 2020)
When a Muslim dies, there are four main things that should be settled upon his death: funeral expenses, debt settlement, will, and farewell. Upon settling the funeral and debt of the dead, estate management is one of the obligations required to be carried out by the heir using Faraid. Nevertheless, based on the recent statistics issued by Amanah Raya Berhad, there are more than RM60 billion worth of properties of the deceased’s in Malaysia that have been frozen from being distributed to the respective heirs. Unfortunately, 95% of the properties belong to Muslims. Among the reasons for the undistributed properties are the unawareness of the heirs, the cost of property claims, and law restrictions. If this situation continuously happens, there will be a waste of capital in the economy. To avoid this problem, hibah (inter vivos) and will were suggested to be used as tools to avoid problems in distributing the wealth and properties to the heirs. However, there are limitations in the use of these tools. Hence, the purpose of this research is to investigate the behavior of Malaysian Muslims in managing their estate specifically on Hibah and further to determine the factors that influence Muslims to choose Hibah. This is an empirical study that employed logit model analysis of data collected from a survey of Muslims in Malaysia. This study manages to collect 406 questionnaires, and based on the result, it shows that income and knowledge are significant in explaining the Muslim behaviour to choose Hibah. This implies that Muslims would be more likely to choose Hibah as to their estate planning if they have more income and knowledge about Hibah, either basic or technical knowledge.